THE WEDDING CEREMONY “GREETING” IN BUKHARA OASIS - Kurbanova, Manzila Bakievna; Orzieva, Kamola Sayidmurodovna (INTERNATIONAL CONFERENCES, 2023)
Based on the ethnic analysis of Bukhara oasis wedding ceremonies, it is stated in the article that they are of great importance in the formation of feelings such as national identity, enjoyment of traditions, and pride. Also, the unique role of the greeting ceremony at the Bukhara oasis wedding is analyzed. The essence of the rituals performed during this ceremony is revealed. It is highlighted that the ceremony of “salomnomakhonlik” is of great importance in the social life of the oasis residents.